Genome-wide analysis of filamentous temperature-sensitive H protease (ftsH) gene family in soybean - Jiabao Wang; Lu Liu; Rui Luo; Qi Zhang; Xinyu Wang; Fenglou Ling; Piwu Wang (BMC Genomics, 2024)
Abstract Background The filamentous temperature-sensitive H protease (ftsH) gene family belongs to the ATP-dependent zinc metalloproteins, and ftsH genes play critical roles in plant chloroplast development and photosynthesis. Results In this study, we performed genome-wide identification and a systematic analysis of soybean ftsH genes. A total of 18 GmftsH genes were identified. The subcellular localization was predicted to be mainly in cell membranes and chloroplasts, and the gene structures, conserved motifs, evolutionary relationships, and expression patterns were comprehensively analyzed. Phylogenetic analysis of the ftsH gene family from soybean and various other species revealed six distinct clades, all of which showed a close relationship to Arabidopsis thaliana. The members of the GmftsH gene family were distributed on 13 soybean chromosomes, with intron numbers ranging from 3 to 15, 13 pairs of repetitive segment. The covariance between these genes and related genes in different species of Oryza sativa, Zea mays, and Arabidopsis thaliana was further investigated. The transcript expression data revealed that the genes of this family showed different expression patterns in three parts, the root, stem, and leaf, and most of the genes were highly expressed in the leaves of the soybean plants. Fluorescence-based real-time quantitative PCR (qRT-PCR) showed that the expression level of GmftsH genes varied under different stress treatments. Specifically, the genes within this family exhibited various induction levels in response to stress conditions of 4℃, 20% PEG-6000, and 100 mmol/L NaCl. These findings suggest that the GmftsH gene family may play a crucial role in the abiotic stress response in soybeans. It was also found that the GmftsH7 gene was localized on the cell membrane, and its expression was significantly upregulated under 4 ℃ treatment. In summary, by conducting a genome-wide analysis of the GmftsH gene family, a strong theoretical basis is established for future studies on the functionality of GmftsH genes. Conclusions This research can potentially serve as a guide for enhancing the stress tolerance characteristics of soybean.